Design of an alternative energy source based on a multistage thermoacoustic engine with external heat supply - Alkina, Aliya; Sarsikeyev, Yermek; Mekhtiyev, Ali; Neshina, Yelena; Mekhtiyev, Ruslan (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers a multistage thermoacoustic engine with an external heat supply, used to convert low-grade heat from solar and geothermal sources into electrical energy. The study [k of improving the efficiency of thermoacoustic engines using low-grade heat sources remains unresolved because of high self-starting temperatures and significant heat loss. This study examines an approach based on the design of a multistage thermoacoustic engine with an external heat supply, which reduces the starting temperature and improves efficiency. To achieve this goal, mathematical modeling was performed in the DeltaEC environment using a linear approximation of Rott equations; a laboratory prototype of an eight-stage engine was designed. The results showed that at a heater temperature of 105°C and an average pressure of 2 bar, an acoustic oscillation frequency of 64 Hz and an electrical power of up to 80 W are achieved with an efficiency of approximately 12%. Distinctive features of the proposed structure include optimized stage and resonator geometry, the use of a traveling acoustic wave, as well as the ability to operate at low heating temperatures, which distinguishes it from existing analogs. It has been established that increasing the stage diameter to an optimal ratio of 10:1 relative to the resonator, improving thermal insulation, and increasing pressure to 8 bar could increase efficiency by up to 40%. The practical significance of this work is its potential for implementing the designed engine in autonomous power supply systems in rural and remote areas of the Republic of Kazakhstan where electricity costs are traditionally higher and fuel delivery is difficult. The results confirm the feasibility of using thermoacoustic technologies for sustainable and environmentally friendly energy supply